Hubungan Kepatuhan Penggunaan Obat dengan Keberhasilan Terapi Pada Pasien Hipertensi Pra Lansia di RSUD dr. Doris Sylvanus Palangka Raya - Sarampang, Mardiyanti; Widiarti, Astri; Kahanjak, Donna Novina (Barigas: Jurnal Riset Mahasiswa, 2024)
Hypertension, known as the silent killer, is the third leading cause of global death in the world. The prevalence of hypertension sufferers in Indonesia is based on the Ministry of Health's Health Research and Development Agency (Balitbangkes) through data from the 2018 Basic Health Research (Riskesdas) currently at 34.1% which has increased from the previous figure in 2013, which was 25.8. One of the diseases experienced by the elderly is hypertension. Hypertension is a disease that requires long-term treatment. One that influences the treatment is patient compliance in taking antihypertensive drugs. Patient compliance in taking medication is very important to achieve therapeutic success, especially in the pre-elderly group. This study aims to determine the relationship between adherence to drug use and the success of therapy in hypertensive patients at dr. Doris Sylvanus Hospital, Palangka Raya. This study uses a quantitative descriptive design, with a Cross Sectional Design approach. Sampling was done by purposive sampling method. A total of 100 samples that met the inclusion criteria were analyzed using the chi square statistical test. This research was conducted at dr. Doris Sylvanus Palangka Raya General Hospital in April-May 2023. This study showed that out of 100 samples, 54 people (54%) had hypertension at the success rate and there were 37 people (37%) hypertension patients who had hypertension. high compliance. There is a relationship between adherence to drug use and therapeutic success in pre-elderly hypertension patients. The results of the analysis showed that the Chi Square test value was 0.001 (P value <0.05) so that there was a relationship between adherence to drug use and the success of therapy in pre-elderly hypertension sufferers at dr.Doris Sylvanus Hospital, Palangka Raya.